A Metastable Crystalline Phase in Two‐Dimensional Metallic Oxide Nanoplates. Issue 7 (17th January 2019) - Liu, Cong; Zheng, Lirong; Song, Qian; Xue, Zhenjie; Huang, Chuanhui; Liu, Lu; Qiao, Xuezhi; Li, Xiao; Liu, Keyan; Wang, Tie
Abstract: A simple method was adopted in which ultrathin cerium oxide nanoplates (<1.4 nm) were synthesized to increase the surface atomic content, allowing transformation from a face‐centered cubic ( fcc ) phase to a body‐centered tetragonal ( bct ) phase. Three types of cerium oxide nanoparticles of different thicknesses (1.2 nm ultrathin nanoplates, 2.2 nm nanoplates, and 5.4 nm nanocubes) were examined using transmission electron microscopy and X‐ray diffraction. The metastable bct phase was observed only in ultrathin nanoplates. Thermodynamic energy analysis confirmed that the surface energy of the ultrathin nanoplates is the cause of the remarkable stabilization of the metastable bct phase. The mechanism of surface energy regulation can be expanded to other metallic oxides, thus providing a new means for manipulating and stabilizing novel materials under ambient conditions that otherwise would not be recovered. Abstract : The metastable bct phase was only observed in ultrathin cerium oxide nanoplates. Thermodynamic energy analysis confirmed that the surface energy of the ultrathin nanoplates is the cause of the remarkable stabilization of the metastable bct phase. The mechanism of surface energy regulation can be expanded to other metallic oxides, thus providing a means for manipulating and stabilizing such materials under ambient conditions.